EFL Students’ Perceptions of AI Chatbots in Learning Speaking Skills - Siti Maysuroh; Zahratul Fikni; Siti Aisyah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The increasing integration of artificial intelligence in education raises questions about how students perceive and engage with AI tools for language learning. This study aimed to explore the perceptions of English education students at Hamzanwadi University regarding the use of ChatGPT in practicing English speaking skills. Using a qualitative descriptive design, data were collected through open-ended questionnaires, classroom observations, and individual interviews with 20 sixth-semester students. The findings revealed that most students held positive perceptions of ChatGPT, citing its accessibility, privacy, and non-judgmental nature as key benefits that enhanced their speaking practice. Furthermore, students reported increased motivation, confidence, and engagement during their interactions with the chatbot, especially due to its 24/7 availability and supportive feedback environment. However, some participants noted limitations in the quality of ChatGPT’s feedback, which occasionally lacked depth or contextual understanding. The findings contribute to AI-assisted language learning literature by emphasizing the potential of ChatGPT to support speaking fluency and learner autonomy, especially when complemented by teacher guidance. This research suggests that integrating ChatGPT into EFL classrooms can create low-anxiety, personalized speaking opportunities, while also highlighting the need for pedagogical scaffolding to optimize its use.